STRATEGI PERSONAL BRANDING DEDI MULYADI MELALUI KEBIJAKAN PANCA WALUYA: ANALISIS SEMIOTIKA - Ummy Hanifah; Mohammad Ismed; Titiek Surya Ningsih (P3M Politeknik Negeri Media Kreatif, 2026)
The development of social media, particularly YouTube, has transformed how public figures construct personal images and communicate public policies. One figure who actively utilized YouTube was Dedi Mulyadi through the Panca Waluya policy, a character education program that involved sending troubled children to military barracks. This study aimed to analyze how Dedi Mulyadi’s personal branding was constructed through the representation of the Panca Waluya policy on his YouTube channel. This research employed a qualitative descriptive approach within a constructivist paradigm and applied Roland Barthes’ semiotic analysis. The data consisted of four selected scenes from Dedi Mulyadi’s YouTube videos, analyzed at the levels of denotation, connotation, and myth. The findings indicated that the Panca Waluya policy was represented as symbols of obedience, care, firmness, and success, constructing the image of Dedi Mulyadi as a paternalistic yet humanistic leader. This study concluded that YouTube played a significant role in shaping the personal branding of public figures through symbolically constructed policy representations.